From Self‐Determination to Offspring‐Determination? Reproductive Autonomy, Procrustean Parenting, and Genetic Enhancement. Issue 6 (27th September 2021) - Rueda, Jon
Abstract : Emerging reprogenetic technologies may radically change how humans reproduce in the not‐so‐distant future. One foreseeable consequence of disruptive innovations in the procreative domain is an increase in the reproductive autonomy of intended parents. Regarding the prospective parental liberty of enhancing non‐health–related traits of the offspring, one controversy has particularly dominated the literature. Does parents' choice of genetically enhancing the traits of their descendants compromise children's future personal autonomy? In this article, I will analyse the main arguments which posit that reprogenetic enhancement could be at odds with the child's future autonomy. I will argue that these objections are ill‐founded. Moreover, I will present other arguments that show that reprogenetic technologies can enhance the autonomy of future children. Autonomy enhancement is a plausible and pro tanto desirable application of emerging reprogenetic technologies.